2015
DOI: 10.1088/1742-6596/582/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of radical pairs dynamics immersed in an ELF-EMF: The effect on hepatocarcinogenesis

Abstract: The most suitable mechanism of action of electromagnetic fields (EMF) on biological systems is the effect on the radical pair (RP) recombination through the Zeeman effect and hyperfine interaction, which changes the rate of reactions or the product distribution. Enzyme reactions with RP intermediates can be altered by EMF, like those catalyzed by cytochrome P450 enzymes (CYP450), a heme-thiolate family protein that detoxifies xenobiotics and involved in chemical carcinogenesis. CYP450 activate chemical carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In our research group, we have implemented the use of an ELF-EMF to study hepatocarcinogenesis in its early stages to assess its cytoprotective effect, both experimentally and theoretically. We proposed that it is possible to deter the carcinogenic process induced by chemical carcinogens in the early stages during enzymatic procarcinogen activation by CYP450 through the modulation of charge migration in the electron transfer reactions involved in oxidation [8,9]. This has been achieved by modulating the magnetic sensitivity of short-lived RP intermediaries produced during the catalytic cycle using ELF-EMF.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our research group, we have implemented the use of an ELF-EMF to study hepatocarcinogenesis in its early stages to assess its cytoprotective effect, both experimentally and theoretically. We proposed that it is possible to deter the carcinogenic process induced by chemical carcinogens in the early stages during enzymatic procarcinogen activation by CYP450 through the modulation of charge migration in the electron transfer reactions involved in oxidation [8,9]. This has been achieved by modulating the magnetic sensitivity of short-lived RP intermediaries produced during the catalytic cycle using ELF-EMF.…”
Section: Introductionmentioning
confidence: 99%
“…In this chapter, we review the experimental and theoretical findings found by our research group within the context of the current knowledge on the cytoprotective effect of ELF-EMF in the early stages of OS induced by chemical carcinogenesis (ChemCar). We use the term cytoprotection because of the conferred protection that dissuades or modulates, controls, or deviates processes originated from bioactivation of procarcinogens, which avoids or diminishes damage to cells or its molecular components [8,9]. On the one hand, we describe and discuss the experimental findings of our group on the effect of daily treatment with 4.5 mT (120 Hz) of ELF-EMF.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations